2022
DOI: 10.3390/polym14153042
|View full text |Cite
|
Sign up to set email alerts
|

Chitosan Effect on Hardening Dynamics of Calcium Phosphate Cement: Low-Field NMR Relaxometry Investigations

Abstract: Calcium phosphate cements are used in dentistry and orthopedics to repair and reconstruct bone defects. The properties of these bone cements can be improved by introducing additives into their composition. One favorable additive is chitosan, which can be beneficial but can also cause considerable damage if it has a high load, thus, limiting its clinical applicability and performance. That is why understanding chitosan’s role in cement composition is an important issue when developing new materials. The present… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
8
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(10 citation statements)
references
References 26 publications
(33 reference statements)
2
8
0
Order By: Relevance
“…The echo trains depicted in Figure 1 indicate a slower hardening process in the case of the C1 sample (Figure 1a) as compared with C2 sample (Figure 1b), which contains chitosan. This observation for longer hardening times is analogous with the previous results on similar samples for shorter evolution times [30]. It is also observed that for both samples, the polymerization process is not completely finalized even after one hour, and this may affect both the absorption and solubility dynamics.…”
Section: Resultssupporting
confidence: 89%
See 3 more Smart Citations
“…The echo trains depicted in Figure 1 indicate a slower hardening process in the case of the C1 sample (Figure 1a) as compared with C2 sample (Figure 1b), which contains chitosan. This observation for longer hardening times is analogous with the previous results on similar samples for shorter evolution times [30]. It is also observed that for both samples, the polymerization process is not completely finalized even after one hour, and this may affect both the absorption and solubility dynamics.…”
Section: Resultssupporting
confidence: 89%
“…Two samples made of calcium phosphate cements, denoted C1 and C2, respectively, were investigated, with the composition comprehensively discussed in our previous work [30]. The samples have the same solid-liquid ratios and identical quantity of liquid components and chemical initiation system.…”
Section: Sample Preparationmentioning
confidence: 99%
See 2 more Smart Citations
“…Obviously, for biomedical or clinical applications it is crucial that their mechanical properties meet the required strict standards. Taking this into account, the toughening of these types of composites is crucial and many research groups have focused on this area, with good and promising achievements [87][88][89]. The strength of composites is also dependent on their pore size and distributions For example, Iqbal et al [90] produced dicalcium phosphate dihydrate (DCPD) composite scaffolds with different DCPD concentrations (0-50 wt%), and reported that the increasing DCPD content resulted in higher crystallinity and reduction in pore size and distribution, observing mainly entwined and closed porosity.…”
Section: Chitosan-based Bioceramic Compositesmentioning
confidence: 99%